Study on the Depth and Evolution of Keyholes in Plasma-MIG Hybrid Welding - Xinglin Miao; Hongtao Zhang; Wenhuan Cao; Zhenyu He; Bo Wang; Fuchen Ge; Jianguo Gao (Crystals, 2023)
Keyholes are very important to the Plasma-MIG hybrid welding process, weld formation, and quality. With the purpose of studying the effect of the main welding parameters (plasma current, MIG current, magnetic field intensity, and welding velocity) on keyhole depth and the interaction among parameter factors, the experiment was designed by the response surface method. In addition, the prediction model with keyhole depth as the response value was obtained. The model shows the important degree of influence of each factor on keyhole depth. It shows that there is an obvious interaction between plasma current and MIG current, while there is no obvious correlation between other parameters. The temperature field of the Plasma-MIG welding process under certain parameters was obtained by using Fluent software for numerical simulation, and the evolution behavior of the keyhole was analyzed. Based on the simulation results, the metal flow mode and the movement mechanism of the keyhole are described.